Involvement of cranial nerves in ATTR Ile127Val amyloidosis - Batista, Jemima A. da Silva [UNESP]; Carrera, Luiza R.; Viriato, Adriele R.F.; Novaes, Marco Antônio C.; Morais, Renato José L. de; Oliveira, Francisco T.O.; Marques, Wilson [UNESP]; Machado-Costa, Marcela Câmara (Elsevier, 2022)
The involvement of cranial nerves is rare in ATTR amyloidosis. However, involvement has occasionally been reported in the p.Val50Met variant, the most commonly studied worldwide. On the other hand, in ATTR p.Ile127Val, an uncommon variant, the cranial nerves IX, X, and XII, are frequently involved. Here, we present a series of cases of ATTR Ile107Val amyloidosis, in which the involvement of multiple cranial nerves V, VII, IX, X, XI, and XII seems to be routinely included in phenotypic manifestations in different phases of clinical evolution, contributing significantly to the resulting disabilities caused by this variant. The recognition of these manifestations enables earlier diagnoses and reduces complications from the involvement of cranial nerves, such as dysphagia and respiratory impairment, which greatly increase the burden caused by the disease and significantly limit the quality of life.
Keywords: Amyloidosis; ATTR; Bulbar involvement; Cranial nerve; Ile107Val; Polyneuropathy